NURSING CARE IN CHILDREN WITH TYPE 2 DIABETES - Gayberdiyeva Khilola Olimjon qizi (Scholar Express Journals, 2025)
Diabetes mellitus is a chronic and metabolic disease that is spreading worldwide and growing younger. The number of cases of this disease is increasing every year. In 2021, 529 million people worldwide were diagnosed with diabetes, and by 2050, this number is expected to reach 1.31 billion. Nowadays, the problem of improper nutrition (fast food, eating a lot of sweets) and obesity among children has increased. This leads to the development of type 2 diabetes. The responsibility of the first link of the healthcare system, nurses, is very important to children with diabetes. The importance of nursing practice and this process in improving the patient is great. This article describes the main processes of care for children with type 2 diabetes and the role of nurses
Keywords: Children with type 2 diabetes; nursing care; healthy lifestyle